Effects of a cafeteria-based sustainable diet intervention on wellbeing at a large German hospital: a quasi-experimental study - Harrison, Laura; Herrmann, Alina; Quitmann, Claudia; Stieglbauer, Gabriele; Zeitz, Christina; Reininghaus, Ulrich; Schick, Anita; Danquah, Ina (BMC public health, 2025)
Sustainable diets are vital to tackle climate change and promote health. They may also offer significant benefits for mental and physical wellbeing. Creating a sustainable food environment at the working place could therefore contribute to the wellbeing of employees. In this quasi-experiment, we investigated effects of providing vegan menus and nutritional information in a cafeteria of Heidelberg University Hospital on mental wellbeing and health-related quality of life (HRQoL) among customers. Regular customers (> one visit/week) in the largest cafeteria (intervention group, n = 121) and in all other cafeterias (control group, n = 128) completed a questionnaire before and after the 3-month intervention period (16/01/2023-06/04/2023). We measured mental wellbeing using the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), HRQoL using the Short Form- 36 Questionnaire (SF-36) and adherence to the Planetary Health Diet (PHD) using a Food Frequency Questionnaire. Difference-in-differences (DID) were calculated for the intervention effects on WEMWBS and SF-36 scores. Cross-sectional associations of the PHD-Index with these scores were calculated at baseline. In this study population (N = 249; women: 65%), the mean baseline WEMWBS was 54.46 (standard deviation, SD: 7.13) in the control group and 55.19 (SD: 6.41) in the intervention group. The difference-in-differences was 0.61 (95% confidence interval, CI: - 0.78, 1.99; p = 0.39). Effects were insignificant for all SF-36 outcomes. Adherence to the PHD-Index was positively associated with self-rated health (beta: 0.48; 95% CI: 0.20, 0.75; p <.001). This worksite cafeteria-based diet intervention yielded nominal improvements in mental and physical wellbeing among customers; this could be mediated by increased adherence to the PHD. These trends warrant verification in larger-sized intervention studies with more intense intervention dosages. Our findings underline the importance of sustainable food environments for planetary health. The protocol was registered at the German-Clinical-Trial-Register on 22/04/2024 (DRKS00032620).
Gesehen am 30.09.2025